Design and analysis of magnetic circuit for mass transfer 6-DOF magnetic levitation platform - Shinan Cao; Pingjuan Niu; Wei Wang; Sha Sheng; Peilai Peng; Wei Song (Heliyon)
Mini/Micro LED is a new display technology, it has advantages of long-life, energy-saving, fast response speed and brightness. The mass transfer speed of Mini/Micro LED is main challenge for its large-scale application. Magnetic levitation platform with long stroke is vital to increase the mass transfer speed. The magnetic circuit is important to improve the stroke of the magnetic levitation platform. The existing magnetic circuit can't decrease the levitation power consumption for long stroke magnetic levitation platform and no evaluation metrics can be used to evaluate the magnetic circuit design. To improve the stroke of magnetic levitation platform, a novel Halbach PM array is proposed and optimized. The εUMFD is first used to evaluate Halbach PM array. The novel Halbach PM is optimized with the εUMFD, the Lhky and the Lhcx is optimized. The result shows that the εUMFD can be improved by increasing the Lhky and decreasing the Lhcx. The passive MB force is increased to 37 N when the εUMFD is 56.7 %. Finally, a novel Halbach permanent magnet array is manufactured and the MFD experiment is done. The result shows that MFD obtained by the three methods are essentially same.